PENGGUNAAN PENDEKATAN KONTEKSTUAL BERBASIS LESSON STUDY PADA PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN AKTIVITAS DAN KOMPETENSI BELAJAR SISWA DI KELAS VIII.3 MTsN LUBUK BUAYA PADANG - Salvina, Salvina; Lufri, Lufri; Zulyusri, Zulyusri (Kolaboratif, 2014)
The biology learning process in class VIII.3 of MTsN Lubuk Buaya Padang was still teacher-centered learning. The learning methods which were used less varied, it made the students got low activities and competence in learning. The were still many students not active, who were reluctant to ask questions and always wait for direction by teacher. This research was designed for improving the studentâ€™s activities and biology learning competence through approachment contextual based lesson study. This was a classroom action research. This was conducted in two cycles in which each cycle consisted of planning, acting, observing and reflecting. The subject of the research was the students in class VIII.3 MTsN Lubuk Buaya Padang. The instruments of the research were observation sheet, a result of learning test and range of notation. The data was collected through observation and a learning achievement test. The data obtained then was analyzed qualitatively and quantitatively. The result of data analysis cycle I and cycle II shows the increase in student learning activity and competence. Learning activities of students increase from 45,70% to 64,67%. Cognitive learning outcomes of students in cycle I and cycle II also increase from 71,79% to 89,7%. Affective learning outcomes of students from 54,7% to 67,14% andÂ psychomotor learning outcomes of students from 73,40% to 76,49%. The teacherâ€™s activities improved from 79,45% to 93,31%. In general, it was concluded that employing the approachment contextual based lesson study in biology learning could improve the learning activities and learning competence of the students in class VIII.3 MTsN Lubuk Buaya.